(60-2x)=(3x+45)

Simple and best practice solution for (60-2x)=(3x+45) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (60-2x)=(3x+45) equation:



(60-2x)=(3x+45)
We move all terms to the left:
(60-2x)-((3x+45))=0
We add all the numbers together, and all the variables
(-2x+60)-((3x+45))=0
We get rid of parentheses
-2x-((3x+45))+60=0
We calculate terms in parentheses: -((3x+45)), so:
(3x+45)
We get rid of parentheses
3x+45
Back to the equation:
-(3x+45)
We get rid of parentheses
-2x-3x-45+60=0
We add all the numbers together, and all the variables
-5x+15=0
We move all terms containing x to the left, all other terms to the right
-5x=-15
x=-15/-5
x=+3

See similar equations:

| -108=4(3x-6) | | 7n+1+n=8n-4 | | 2y+80=180 | | 12x+2=9x-4 | | -3t-20-20=20+2t | | -x^2+5x+200=0 | | n(18)+5(n+1)=97 | | 12s−3s3=012s−3s3=0 | | 5(-2+n)=91+(-n+1) | | 2(x13)-4=12 | | 9x-4=12x+2 | | 8x+31=x | | 44+44+14x-6=180 | | 2m+6=3m-7 | | 4x-2=-17 | | 10u+7=(u-4)-9 | | -3s+4=19-2s | | b/3=4/3 | | 360=12x-4+18x+4+15x+10+5x | | 6w=5w+14 | | -9-10v=-5v+5-7v | | 20u^2-55u=0 | | 6m+10=-2+1 | | -6+6y=-9 | | 20^2-55u=0 | | -9−10v=-5v+5−7v | | 936=(2x-4)(x+8) | | 6y+7=2y+43 | | 7-6b+10=-10-3b | | 1/7x=0.25x-2.75 | | 8(3-6n)=264 | | 12n=3+(2(n+1)) |

Equations solver categories